Canadian Manufacturing, U.S. R&D Spillovers, and Communication Infrastructure - Bernstein, Jeffrey I. (The Review of Economics and Statistics, 2000)
Canada is highly integrated with the U.S. economy. This north-south link, coupled with its east-west dimension, also renders Canadian production dependent on communication infrastructure. We investigate the influence of research and development (R&D) spillovers from U.S. manufacturing and Canadian communication infrastructure on Canadian manufacturing. Canadian production becomes relatively more R&D-intensive from communication spillovers. However, manufacturers substitute knowledge from U.S. spillovers for domestic R&D. U.S. spillovers cause production to become more plant- and equipment-intensive. Spillovers also enhance productivity. Communication infrastructure accounted for 8.5% of the growth, with the major source emanating from U.S. spillovers. They contributed 76% of the gains.